Travel advisories – destabilising diplomacy in disguise. Issue 1 (2nd January 2017) - Deep, Aman; Johnston, Charles Samuel
ABSTRACT: In developed countries, travel advisories are generally viewed as legitimate by the travelling public. This paper is constructed around the opposite position – the travel advisory often represents an attempt to politically and/or economically destabilise the developing-nation destination through disruption of tourism. As a conceptual paper, we reference academic literature to create a destabilisation-to-re-stabilisation sequence. We examine five aspects. We begin by discussing how the right to travel is guaranteed in international agreements. We develop a typology of the ways travel advisories have been misused, which shows how individual travel decisions can be destabilised. We show how this destabilises developing nations and conclude with a possible strategy to re-stabilise the situation. In the paper, we advance five models we believe help generalise our discussion to a wider range of cases. The paper thus has significant practical implications for countries being adversely affected by politically and economically motivated travel advisories.